Parasitismo natural de ovos do curuquerê-do-algodoeiro por trichogramma pretiosum (hymenoptera: Trichogrammatidae) em diferentes estágios fenológicos de variedades de algodoeiros em ipameri, go - Costa, Lílian Lúcia [UNESP]; Funichello, Marina [UNESP]; Busoli, Antonio Carlos [UNESP] (My University, 2010)
The cotton can be damaged by many pests, standing out among them cotton leafworm, responsible for major losses in production, if not controlled properly. A group of natural enemies is the most studied of the family Trichogrammatidae, mainly species of the genus Trichogramma, because of its importance in biological control at the initial stage of development of their hosts. In order to study the natural egg parasitism of Alabama argillacea (Hübner, 1818) (Lepidoptera: Noctuidae) by Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae) in different phenological stages of transgenic and conventional varieties of cotton (Gossypium hirsutum L.) in the region of Ipameri, GO, it was carried out this experiment from december 2007 to april 2008, in the UEG, State of Goias. The experimental design was in randomized blocks with five treatments consisting of the conventional varieties DeltaOPAL, FMX 966, FMX 993, FMX 910 and NuOPAL transgenic variety, in four replications. In the beginning of oviposition of the A. argillacea it was started the 27 old days plant and the parasitism increased as the availability of eggs of the host, regardless of variety. It was found that the varieties over the vegetative cycle did not show statistical differences on the preference for oviposition by the moth neither on the parasitism. The level of parasitism of eggs of A. argillacea by T. pretiosum varied depending on the density of eggs on plants, not in terms of varieties and phenological stages.
Natural egg parasitism of cotton leafworm by trichogramma pretiosum (hymenoptera: Trichogrammatidae) in different phenological stages of cotton varieties in ipameri, go
Keywords: Alabama argillacea; Gossypium hirsutum; Natural biological control